International Humanitarian Law II: The Principles of International Humanitarian Law - Hassanová, Rebecca Lilla (International Criminal Law, Humanitarian Law and Refugee Law From The Perspective of Human Rights Law, 2026)
The following chapter analyses the legal status and practical function of the core principles of international humanitarian law within the broader system of international law. It explains how these principles operate both as gap-filling and interpretative tools and as norms rooted in customary law as well as in treaty provisions. The chapter primarily examines the four foundational principles of the system: military necessity, humanity, distinction, and proportionality tracing their historical development, main elements and limitations. The text highlights how they structure targeting decisions, protect civilians and persons hors de combat, and guide legal assessment where treaty rules are ambiguous or incomplete. Their flexible character ensures their continued applicability as guiding norms, particularly in modern forms of warfare.Keywords: international humanitarian law, principle of military necessity, principle of humanity, principle of distinction, principle of proportionality